SAT0200 Long term safety of filgotinib in the treatment of rheumatoid arthritis: week 108 data from a phase 2b open-label extension study. (12th June 2018) - Westhovens, R.; Alten, R.; Winthrop, K.; Greenwald, M.; Ponce, L.; Enriquez-Sosa, F.; Stanislavchuk, M.; Mazur, M.; Spindler, A.; Cseuz, R.; Nikulenkova, N.; Glowacka-Kulesz, M.; et al.
Abstract : Background: Filgotinib (FIL) is an orally administered, selective inhibitor of Janus Kinase 1 (JAK1) in Phase 3 development for the treatment of rheumatoid arthritis (RA). Objectives: Assess the long-term safety and efficacy of FIL in the DARWIN 3 open-label extension study. Methods: Two 24-week Phase 2b studies were completed in patients (pts) with moderately to severely active RA (DARWIN 1, DARWIN 2; Ref 1, 2). Following study completion, pts were offered FIL in the ongoing DARWIN 3 extension study: 100 mg QD (US males), 200 mg QD, or 100 mg BID. This report summarizes safety data from the first dose of FIL in the DARWIN program to 11 Oct 2017 and efficacy data from the DARWIN 3 baseline visit to Week 108, which all ongoing pts have completed. Results: Of 877 pts, 790 (90%) completed DARWIN 1/2, and 739 (84%) enrolled in DARWIN 3; 603 (82%) were female, mean age 53 years. At analysis, 491/739 (66%) were on study. Cumulative patient years of exposure (PYE) was 1931, median time on study drug was 1072 days. Key data are summarized in table 1. 87%, 68%, and 48% of pts achieved ACR20/50/70, respectively, and 72% achieved DAS28-CRP≤3.2 (by observed case analysis). Conclusions: Filgotinib long-term RA data demonstrates an acceptable safety and durable efficacy profile. References: [1]Westhovens R, et al. Ann Rheum Dis2017;76:998–1008. [2]Kavanaugh A, et al. Ann Rheum Dis2017;76:1009–1019. Disclosure of Interest: R. Westhovens Grant/research support from: Galapagos and Celltrion, Roche and BMS, Consultant for: Galapagos and Celltrion, Roche and BMS, R. Alten Grant/research support from: Galapagos/Gilead, K. Winthrop Consultant for: Pfizer, Lilly, Galapagos, Gilead, AbbVie, M. Greenwald Grant/research support from: Gilead, L. Ponce: None declared, F. Enriquez-Sosa: None declared, M. Stanislavchuk: None declared, M. Mazur: None declared, A. Spindler: None declared, R. Cseuz: None declared, N. Nikulenkova: None declared, M. Glowacka-Kulesz: None declared, I. Szombati: None declared, A. Dudek: None declared, N. Mozaffarian Shareholder of: Gilead, Employee of: Gilead, J. Greer Shareholder of: Gilead, Employee of: Gilead, R. Kunder Shareholder of: Gilead, Employee of: Gilead, D. An Shareholder of: Gilead, Employee of: Gilead, P. Harrison Shareholder of: Galapagos, Employee of: Galapagos, A. Van der Aa Shareholder of: Galapagos, Employee of: Galapagos, A. Kavanaugh Consultant for: Galapagos, M. Genovese Consultant for: Gilead, Galapagos, Abbvie, Lilly, Pfizer